Techniczne aspekty produkcji biodiesla - nowe kierunki badań - Pińkowska, Hanna (Technical Aspects of Biodiesel Production - New Research Areas, 2008)
Biodiesel, which is derived from triglicerydes by transesterification with alcohols (methanol, ethanol) using alkali-catalysts, has attracted considerable attention as renewable, biodegradable, and non toxic fuel. This paper reports a bibliography survey on new technical trends in biodiesel production. The review also describes the preparation of biodiesel using microwave heating, and ultrasonic or hydrodynamic cavitation. The review covers current and potential new low-cost raw feedstocks for making biodiesel, heterogeneous and enzymatic catalysts, and recent progress in supercritical fluid science for biodiesel production via non-catalytic esterification and transesterification reactions. The most important achievements and examples are described in detail. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 152-172